2016
DOI: 10.3347/kjp.2016.54.6.797
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigation of Asymptomatic Dogs with Leishmania Infection in Southwestern China Where Visceral Leishmaniasis is Intractable

Abstract: Heishui county, located in northwest Sichuan province, southwestern China, is an endemic area of zoonotic visceral leishmaniasis (VL) and is the most intractable area. VL is never destroyed in it. Asymptomatic dogs (Leishmania parasites have been diagnosed but clinically healthy) are considered to be a potential reservoir host in zoonotic VL area, and most can lead to infection of individuals, that is a new challenge for controlling VL in humans. The present study aimed to assess the Leishmania infection rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…High Leishmania spp. infection rate was detected in local dogs, so the number of human VL cases can be reduced by the elimination and suppression of local dogs [11,25,26]. The dog was the principal reservoir host in this epidemic area.…”
Section: Comprehensive Results Of Yangquanmentioning
confidence: 99%
“…High Leishmania spp. infection rate was detected in local dogs, so the number of human VL cases can be reduced by the elimination and suppression of local dogs [11,25,26]. The dog was the principal reservoir host in this epidemic area.…”
Section: Comprehensive Results Of Yangquanmentioning
confidence: 99%
“…We have veri ed dogs as a reservoir host of Leishmania; it may be the principal reservoir and the key to human VL cases in the region. A high Leishmania infection rate has been detected in dogs in the past, and human VL cases have been reduced after the elimination and suppression of local infected dogs (11,25,26). Recently, VL cases in extension region of the Loess Plateau, China reappear after the disease eradication for 20 years, which posed a challenge for control.…”
Section: Discussionmentioning
confidence: 99%
“…High Leishmania spp. infection rate was detected in local dogs in the past, and human VL cases were reduced after the elimination and suppression of local infected dogs [11,25,26]. Recently, VL cases in extension region of the Loess Plateau, China reappear after the disease eradication for 20 years, which posed a challenge for control.…”
Section: Comprehensive Detections From Yangquanmentioning
confidence: 99%
“…It has been reported that the positive rate of Leishmania spp. in dogs was above 50% in Jiuzhaigou Sichuan, 41.9% in Heishui Sichuan, and 77.21% in Wenxian Gansu, China [11,25,41]. In Shanxi Province, there was only one investigation in 1959, in which the Leishmania positive rate in dogs was 0.01% [16].…”
Section: Comprehensive Detections From Yangquanmentioning
confidence: 99%